Anisotropic acoustic phonon polariton-enhanced infrared spectroscopy for single molecule detection. Issue 29 (20th July 2021) - Lyu, Wei; Teng, Hanchao; Wu, Chenchen; Zhang, Xiaotao; Guo, Xiangdong; Yang, Xiaoxia; Dai, Qing
Abstract : Highly confined anisotropic acoustic phonon polaritons in a monolayer α-MoO3 /air nanogap/Au heterostructure largely enhance single molecule detection with nano-FTIR. Abstract : Nanoscale Fourier transform infrared spectroscopy (nano-FTIR) based on scanning probe microscopy enables the identification of the chemical composition and structure of surface species with a high spatial resolution (∼10 nm), which is crucial for exploring catalytic reaction processes, cellular processes, virus detection, etc . However, the characterization of a single molecule with nano-FTIR is still challenging due to the weak coupling between the molecule and infrared light due to a large size mismatch. Here, we propose a novel structure (monolayer α-MoO3 /air nanogap/Au) to excite anisotropic acoustic phonon polaritons (APhPs) with ultra-high field confinement (mode volume, V APhPs ∼ 10 −11 V 0 ) and electromagnetic energy enhancement (>10 7 ), which largely enhance the interaction of single molecules with infrared light. In addition, the anisotropic APhP-assisted nano-FTIR can detect single molecular dipoles in directions both along and perpendicular to the probe axis, while pristine nano-FTIR mainly detects molecular dipoles along the probe axis. The proposed structure provides a way to detect a single molecule, which will impact the fields of biology, chemistry, energy, and environment through fundamental research and applications.